The effect of external factors on the students' acceptance of virtual learning. - Aleshidi, Hamad A.; Zeki, Akram M. (IIUM Press, 2011)
The rapidly growing popularity of E-Learning has introduced new terms to education, as virtual learning. The success of a virtual learning environment (VLE) depends on a considerable extent of student acceptance and use of such an e-Iearning system. The current study introduces an overview of the Technology Acceptance Model (TAM). Furthermore, it builds a conceptual model to explain the differences between individual students in the level of acceptance and use of a VLE. This model is an extension of TAM. The primary findings of the study show that perceived of peer encouragement (PPE) has direct influence on the students' attitude to use virtual learning. Computer self-efficacy (CSE) and enjoyment (EN) have direct effect on the students' intention to use virtual learning, whilst, the cultural factor (CF) has indirect effects mediated by TAM.